A Review on Medhya Karma of Selected Ayurvedic Drugs Based on Dravyaguna Principles - Kushwaha, Angad Kumar; Kumari, Sarita; Singh, Mahendra Prasad; Ranjan, Raman (Journal of Neonatal Surgery, 2025)
Medhya Karma, referring to the enhancement of intellect, cognition, and memory, is a fundamental therapeutic category in Ayurveda. Several Medhya Dravyas are traditionally recognized for their efficacy in promoting mental functions and neuropsychological health. This review critically analyzes the Dravyaguna aspects (Rasa, Guna, Veerya, Vipaka, and Karma) of selected Medhya herbs including Mandukaparni (Centella asiatica), Brahmi (Bacopa monnieri), Shankhapushpi (Convolvulus pluricaulis), and Jyotishmati (Celastrus paniculatus), correlating classical Ayurvedic principles with contemporary neuropharmacological research. Emphasis is placed on their nootropic, adaptogenic, and antioxidant properties that align with the concept of Medhya Karma. This integrative analysis provides a deeper understanding of these herbs and promotes their rational application in managing cognitive disorders and enhancing mental performance